The black sea: the energetic corridor between Europe and Asia - Brocate Pirón, Roberto Luis; Rios Sierra, Jerónimo (Reflexión Política, 2016)
The Black Sea is one of the most important geostrategic enclaves in the oil and gas connection linking Asia with Europe and Russia. However, the presence of Turkey on the Bosphorus Strait directly affects how the geo-strategic interactions of the region develop. The crisis in Ukraine has spurred Turkish-Russian relations, positioning the country as a key player in the gas transit to Eurasia and projecting the aspirations of the Kremlin, under President Vladimir Putin has sought to regain an influential weight in the region - as shown by the crisis in Georgia or, more recently, Crimea - especially in the Black Sea and the Caspian Sea. Thus, the following work seeks to put a little light on new relationships and geopolitical aspirations, especially in Russia and Turkey and, likewise, have a direct impact on the European context.